Describiendo el clúster de la Bolsa de Valores de El Salvador - Rivera, Giovanny; Flores, Rodrigo; Orantes, Edgar (Empresa y Sociedad, 2024)
The Stock Exchange Market of El Salvador is the only entity in the country that facilitates access to the market for domestic private debt issues, equity issues and repurchase agreements. In addition, it is the owner of the only central securities depository in the country, “Central de Depósito de Valores, S.A. de C.V.” (Cedeval; classified as ‘EAA + (slv)’ by Fitch Ratings). Also, the entity is responsible for providing participants in the stock market with a service platform in accordance with the legal requirements dictated by the Superintendency of the Financial System (SSF, by its acronym in Spanish). Through its subsidiary, “Cedeval”, offers services for the deposit, custody and administration of securities through an electronic system, since 1998. The purpose of this study was to describe the configuration of the El Salvador Stock Exchange cluster, using the tools of the competitiveness diamond, the value chain and the cluster map.